2000
DOI: 10.1002/1097-4644(20010301)80:3<313::aid-jcb30>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperprolactinemia on testosterone production in rat Leydig cells

Abstract: The pathogenesis of hyperprolactinemia (hyperPRL) induced hypogonadism has been suggested to be related with a dysfunction of hypothalamus-pituitary-testis axis. While the direct inhibitory effects of prolactin (PRL) on testosterone (T) release have been demonstrated, the mechanism is still unclear. Our previous study demonstrated a diminished T release in the testicular interstitial cells (TICs) from the anterior pituitary (AP)-grafted rats as compared with the control, and the pattern was in agreement with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The increase in prolactin secretion in spring may cause macrophages to reduce HSL protein expression and activity in the interstitium, and this in turn may be one of the causes that would decrease testosterone synthesis by Leydig cells. The report that prolactin induces accumulation of cholesterol esters in response to LH stimulation [67] and the observation that prolactin inhibition of testosterone production involves interstitial cells other than Leydig cells in the rat [68] are in agreement with this hypothesis.…”
Section: Relationship Of Testicular Hsl To Serum Pituitary Hormone Cosupporting
confidence: 76%
“…The increase in prolactin secretion in spring may cause macrophages to reduce HSL protein expression and activity in the interstitium, and this in turn may be one of the causes that would decrease testosterone synthesis by Leydig cells. The report that prolactin induces accumulation of cholesterol esters in response to LH stimulation [67] and the observation that prolactin inhibition of testosterone production involves interstitial cells other than Leydig cells in the rat [68] are in agreement with this hypothesis.…”
Section: Relationship Of Testicular Hsl To Serum Pituitary Hormone Cosupporting
confidence: 76%
“…Thus, the increase of Ang II in the 2K/1C rats could be, indirectly, one of the causes for the reduction of plasma testosterone in these animals. Moreover, high plasma PRL can reduce the sensitivity in Leydig cells to the stimulatory action of LH and thus reduce the secretion, but not the synthesis, of testosterone (Huang et al, 2001). Additionally, long-term hyperprolactinemia reduces LHRH release and thus decreases plasma testosterone (Nasello et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal and human studies have indicated that hyperprolactinemia is related to plasma-androgen concentrations, although findings are controversial (38)(39)(40). Because both 5a-R1 and 5a-R2 genes are positively regulated by T, the most abundant androgen (41), we measured plasma T levels in controls and sulpiride-treated rats.…”
Section: Discussionmentioning
confidence: 99%